Why the Procession of Death in 2020 Covid-19 Great Epidemic: An Islamic Analysis - Hossain, Md Kohinoor (IAIN Samarinda, 2020)
Only love to almighty Allah is the greatest love. From ages to ages, Allah has sent his messengers to preach only love to Him. Many destruction, disruptions and explosion have been occurred in this world. This paper tries to explore about the causes the great disasters in the world. The global people when they lead an invalid way, there occurs a terrible crisis. None of the world saves it. Only Allah can save the global people. Today, the present world is full of share-ism, idolatry-ism, usury-ism, zakat-free-ism, killing-ism, injustice-ism and inhumanity-ism. They practice about Gods and Goddesses. They believe that the sun, the moon, the stars, the trees, the stone, the angels, the jinn and other animals can reach to Allah. They are the dearest persons who are God, Gods, Goddess and Goddesses related. Above eleven millions people think and say that there is no creator of the universe. It is operating as automated. Marriages and sexism are into human to animal. They practice as same-sex, polygamy, polygyny and polyandry. Most of the global people pray to Materials, Death Guru, God, Gods, Goddess, Goddesses, Peer, Saai, Baba, Abba, Dihi Baba, Langta Baba, Khaja Baba, Joy Guru, Joy Chisty, Joy Baba Hydery, Joy Maa Kali, MaaDurga, MoorshidKibla, Baba HaqueBhandary, Joy Ganesh Pagla, Joy DeawanBaggi, Joy Chandrapa, Joy Sureshwaree, FooltaliKebla, SharshinaKebla, FoorfooraKebla, Joy Ganapati, Joy Krishnan, Joy Hari, Joy Bhagabanand Mazzarians. The new religions have preached in the world such as Baha’i, Kadyany, Khaljee, Din-E-Elahi, Brahma and Humanism. The world is full of Shirkism, Moonafikism, Goboatism, Bohtanism, Mooshrikiaism, Oathlessism and Khianotkariism. In the past undetermined civilizations have been vanished but none can save the civilization. This Covid-19 great destruction is human made. It is from climate change which comes to the global people as a great curse.